Drivers and Motivations of Outward FDI in EMEs: A Comparison in Cross-border M&A between China and India - ZHAO, YUE (2014)
This paper comparatively investigates the major factors that determine the strategic international extension by emerging market firms. By means of selecting four cross-border merger and acquisition (M&A) cases from China and India, the paper provides an integrative comparison based on general theories and empirical studies to justify how institutional factors drive the determinations of emerging market enterprises’ (EMEs) strategic decisions as well as the factors to motive international expansions. In addition, the paper analyzes challenges during and after the deal by multinational enterprises (MNEs) in cases and notes some further suggestions after comparative study between Chinese and Indian cross-border M&A cases.